Safety Risk of Flammable and Explosive Dangerous Goods through the Ship Lock. Issue 1 (August 2020) - Xie, Tiansheng; Han, Chao; Wang, Guobo; Fengyun, Chen
Abstract: Based on the analysis of the current situation on flammable and explosive dangerous goods passing through the Three Gorges ship lock, evaluate leakage, fire, and explosion hazards through typical accident simulation calculations to find out the hazardous characteristics and safety risks of flammable and explosive dangerous goods through the Three Gorges ship lock. The study indicates the main safety risks of flammable and explosive dangerous goods passing through the ship lock are ship collision, grounding, leakage, fire and explosion, as well as the facilities strength declining in lock chamber, cracks or other structural destructions due to the long-time high temperature under flame or overpressure of the explosion.